Chemical composition, antifungal activity, antifungal mechanism and interaction manner of the fatty acid of Prunus mahaleb L. with fluconazole. Issue 10 (3rd October 2022) - Erdogan Eliuz, Elif Ayşe; Yabalak, Erdal; Gökşen, Gülden; Ayas, Deniz
ABSTRACT: The interaction manner of Prunus mahaleb L. ( P. mahaleb ) seed oil (MSO) and fluconazole (FLC: antimycotic) combinations (MSO*FLC) against C. albicans and C. parapsilosis were evaluated using the microdilution technique. The most representative compounds of mahaleb oil were found to be conjugated linolenic acid (34.39%), oleic acid (31.76%), and linoleic acid (25.54%) by GC-MS. In antimicrobial activity study, P. mahaleb had an inhibition zone (IZ) of C. albicans and C. parapsilosis with 6.89 mm and 11.39 mm and a minimum inhibitory concentration (MIC) with 35.3 µgmL −1 and 23.9 µgmL −1, respectively. The strongest indifferent effect was observed as 57.14% for C. albicans and 100% for C. parapsilosis in fluconazole-mahaleb oil combinations. An increase in DNA and protein leakage was observed when yeast was exposed to the FA. The destruction on the cell surface was visualized using Scanning Electron Microscopy (SEM) analysis.